PENGARUH PRICE DISCOUNT, BONUS PACK, DAN SALES PROMOTION TERHADAP IMPULSE BUYING PADA GIANT PEKANBARU - Jufri, Detry Septiyani; Kartikowati, Sri; Indrawati, Henny (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The rapid retail business in Pekanbaru makes competition between retail increasingly increased. One way to do to pull consumers by way of promotion sale in the figure. The promotion of the sale in the store will make the impulse buying of consumers more easily formed. This research aims to determine the effect of price discounts, bonus packs, and sales promotion on impulse buying. The population of this research were all Giant Pekanbaru consumers in 2019. samples of 100 respondents were taken using the Slovin formula with the accidental sampling method. Data is collected using a questionnaire, then analyzed by a multiple linear regression method. Based on the research, the results show that price discounts, bonus packs, and sales promotion have a significant effect on impulse buying. The variable that has the greatest regression coefficient is the bonus pack. That is, impulse buying is more influenced by variable X2 (bonus pack) compared to other variables. The better the bonus pack that is applied or given, the more impulse buying increases.Key Words: Price Discount, Bonus Pack, Sales Promotion, and Impulse Buying